Effects of APOE4 on Alzheimer's disease, Lewy body disease, cerebral amyloid deposition and cognitive dysfunction: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Jung, Jin Ho; Jeong, Seong Ho; Jeon, Seun; Baik, Kyoungwon; Lee, Yang Hyun; Chung, Seok Jong; Yoo, Han Soo; Sohn, Young H.; Lee, Phil Hyu; Ye, Byoung Seok
Abstract: Background: We investigated the effects of apolipoprotein E e4 allele ( APOE4 ) on the risk of Alzheimer's disease (AD) and/or Lewy body disease (LBD), cerebral amyloid deposition, and cognitive dysfunction. Method: We consecutively recruited 131 control subjects and 208 (110 non‐demented and 98 demented) patients with AD and/or LBD. Patients were categorized into typical AD (pure AD and Lewy body variant of AD), typical LBD (pure LBD and LBD with amyloid deposition), and typical AD with LBD based on clinical features and biomarker evidence from 18 F‐Florbetaben (FBB) positron emission tomography (PET) and dopamine transporter PET. Logistic regression analysis was performed to investigate whether APOE4 increased the risk for each disease. General linear models (GLMs) were performed to investigate the independent and interaction effects of APOE4, typical AD and typical LBD on cerebral FBB deposition, cross‐sectional cognition and the rate of longitudinal cognitive decline. Result: APOE4 increased the risk of pure AD, AD with DLB, Lewy body variant of AD, and DLB with amyloid deposition, but did not increase the risk of pure LBD. In overall participants, APOE4 increased the risk of typical AD, but not typical LBD. APOE4, typical AD and typical LBD were positively associated with occipital FBB deposition; typical LBD was associated with higher occipital FBB deposition in the absence of typical AD; and APOE4 was associated with higher occipital FBB deposition in the presence of typical LBD. In GLMs for cross‐sectional cognition, APOE4 was associated with lower scores in verbal memory tests and higher clinical dementia rating sum of boxes (CDR‐SOB); it was associated with higher CDR‐SOB in the presence of typical LBD and lower scores in verbal memory tests in the presence of typical AD. APOE4 had no significant effects on the rates of longitudinal cognitive changes. Conclusion: APOE4 is associated with increased risks of AD and amyloid deposition but not with LBD. APOE4 and typical LBD are independently and synergistically associated with occipital amyloid deposition. APOE4 interacts with typical AD on poor memory function and interacts with typical LBD on higher CDR‐SOB cross‐sectionally, but did not have significant effects on longitudinal cognitive decline.